DETERMINAN CASH HOLDING PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2016-2018 - Mohamad Ali (2020)
This research is a quantitative study that aims to determine the effect of net working capital, leverage, and cash flow on cash holding. In this study using the Packing Order Theory and Population in this study only took on companies in the Property and real estate sector that were listed on the Indonesia Stock Exchange (BEI) during the period 2016 to 2018. This study used the Purposive Sampling technique which means the selection of sample criteria was in accordance with we want so we can get a sample of 130 research data. The hypothesis in this study was tested by Multiple Linear Regression Analysis techniques with a Significance level of 5%. The results obtained from this study are net working capital, leverage, and cash flow have a significant positive effect on cash holding.